Hybrid metal nanostructure arrays for colour printing - Bradley, Louise (My University, 2016)
Nanoscale metasurfaces have become an area of growing interest in recent years with the promise of new functionalities. One area that has received a lot of attention is sub-diffraction limit printing. We demonstrate the fabrication of a novel hybrid Au-Ag metal nanoparticle array design on an ultra-thin film propylene polymer material. The design presented generates strong colours due to the plasmonic response and coupling between the two metallic components. It is sensitive to the polymer layer thickness, and it is shown that by tuning this layer thickness, the colour response of the nanostructure can be carefully engineered. We determine the effect fabrication has on the optical properties of the polymer material at these ultra-thin thicknesses, < 200 nm. The fabrication of violet, cyan and red colour pixels using an Au nanoparticle array and Ag back-reflector is demonstrated. We utilise colour conversion software to convert spectra of fabricated samples to RGB values on the CIE 1931 colour space and values agree with observed colour from optical microscope images.
18th International Conference on Transparent Optical Networks (ICTON)
Keywords: Hybrid nanostructure; Plasmonic array; Localised surface plasmon resonance; Colour generation